Aristophanes: Thesmophoriazusae: Aristophanes: Thesmophoriazusae. Edited with Introduction and Commentary. Colin Austin & S. Douglas Olson. 2004 Oxford University Press. - Lech, Marcel Lysgaard (AIGIS, 2024)
Intet.